The impacts of corruption and environmental degradation on foreign direct investment: new evidence from the ASEAN+3 countries - Mohd Shahidan Shaari; Miguel Angel Esquivias Padilla; Abdul Rahim Bin Ridzuan; Nor Fadzilah Zainal; Lilik Sugiharti (Cogent Economics & Finance, 2022)
Foreign direct investment (FDI) plays a vital role in boosting economic growth and providing more job opportunities. Hence, it is imperative to investigate the factors that can spur FDI inflows in the Southeast Asia region (ASEAN) and its three largest trading partners: China, Japan, and South Korea (ASEAN+3). Besides, whether corruption can boost or decrease FDI inflows, and whether larger environmental degradation triggers FDI inflows have been sparsely explored by previous studies. The panel Autoregressive Distributed Lag (ARDL) approach is employed to analyze the period from 1995 to 2020. The results show evidence of the grabbing hand hypothesis in ASEAN+3 as decreasing corruption can positively impact FDI inflows in the long run. However, the results support that increasing environmental degradation has spurred FDI in the region, suggesting reformulating investment promotion policies towards more environmentally friendly ones. These findings are important for policymakers to formulate the right policies for boosting FDI. Punishment for those who act in a corrupt manner may act as a deterrent to would-be offenders. Using more renewable energy could help to reduce environmental degradation and boost FDI simultaneously.
Keywords: 330; clean energy; corruption; energy consumption; environmental degradation; FDI; infrastructure investment; market size; trade openness